Factor affecting adoption social media in business among young entrepreneurs: using the TAM model - Ng, Qing Xuan (2022)
Social media has now become a trend and a critical strategy movement fo businesses. Hence th r is research’s primary objective is to explore the importance factors affecting the adoption of social media in business among young entrepreneurs in Malaysia in order to determine their perceptions and behavioural intention. Besides, Technology Acceptance Model (TAM) was used study the relationship between perceived usefulness (PU), perceived ease of use (PEOU) and trust (T) and behavioural intention (BI) to adopt social media in business. Moreover, a total of 250 of survey questionnai res were collected from the respondents in Klang Valley using convenient sampling technique. All quantitative data obtained were analyzed by using Statistical Package for Social Science (SPSS) version 26 to perform descriptive analysis, pilot test, reliabi lity test, and inferential analysis. However, all the results demonstrated that all of the independent variables (PU, PEOU, and T) have a significant positive relationship with the dependent variable (BI toward the adoption social media in business). Thi s study gives a clearer picture for the Malaysia government and software developers regarding the factors that affect the young entrepreneurs’ intention to use social media in their business. Lastly, limitations encountered throughout the research have bee n identified, and recommendations for future researchers to overcome the limitations have been provided. This research can be a thesis or a reference that gives researchers more information when they want to conduct similar research in the future. xvi